2014
DOI: 10.1159/000363061
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Immuno-Endocrine Modulation in Marathon Runners

Abstract: Objective: Sports practice alters the homeostasis of athletes. To achieve homeostatic equilibrium, the integrated action of the neuroendocrine and immune systems is necessary. Here we studied the relation between cytokines, hormones and mood states in marathon runners. Methods: A total of 20 male recreational marathon runners (mean age = 35.7 ± 9 years) and 20 male sedentary individuals (mean age = 35.5 ± 7 years) were recruited. We compared the serum levels of growth hormone (GH), cortisol and interleukins 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 40 publications
1
21
0
2
Order By: Relevance
“…A previous study by our group [22] on marathon runners showed that the volunteers had elevated levels of IL-10, IL-8, and growth hormone before the race, suggesting that these cytokines act as protective mechanisms of the central nervous system when submitted to strenuous exercise.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by our group [22] on marathon runners showed that the volunteers had elevated levels of IL-10, IL-8, and growth hormone before the race, suggesting that these cytokines act as protective mechanisms of the central nervous system when submitted to strenuous exercise.…”
Section: Discussionmentioning
confidence: 99%
“…It has been long demonstrated that exercise training induces an alteration in cytokine profile [13][14][15]. However, no evidence could be found in the literature of any study correlating RE to IL-6, a modulatory cytokine, in marathon runners.…”
Section: Discussionmentioning
confidence: 99%
“…22 Interleukin 10 (IL-10) is a cytokine that plays an anti-inflammatory role in response to exercise, as well as acting in the brain and behavior, improving mood states. [22][23][24][25] In an attempt to understand these aspects, we proposed to evaluate the levels of anxiety and their connection with IL-10 in a female soccer player group, presenting or not PMS, in four moments: before (pre) and after (post) a simulated game and during the two phases of the menstrual cycle: follicular and luteal.…”
Section: Introductionmentioning
confidence: 99%